2019
DOI: 10.25004/ijpsdr.2019.110401
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activity of different plant parts of Anacardium occidentale L. and Mangifera indica L.: a comparative study

Abstract: Anacardium occidentale L. and Mangifera indica L. has been used worldwide both for pharmaceutical, food and cosmetic industries due to the presence of biological activities of some of its metabolites. The present study comprises the correlation of antioxidant activity and antimicrobial activity in ethyl acetate extract of young leaves and bark of A. occidentale and M. indica. The activity of 1, 1-diphenyl-2-picrylhydrazyl (DPPH) on radical scavenging effect of the extracts was carried out by spectrophotometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…In 2016, a study conducted by Da Silva et al, [30] showed that Anacardium occidentale stem barks and leaves have the similar antioxidant activity with IC50 of 1.12 µg/mL and 1.47 µg/mL, respectively. However, the findings of Sija et al [31] have shown that the young leaves have a higher antioxidant activity than stem barks.…”
Section: Total Polyphenol and Flavonoid Contentsmentioning
confidence: 94%
“…In 2016, a study conducted by Da Silva et al, [30] showed that Anacardium occidentale stem barks and leaves have the similar antioxidant activity with IC50 of 1.12 µg/mL and 1.47 µg/mL, respectively. However, the findings of Sija et al [31] have shown that the young leaves have a higher antioxidant activity than stem barks.…”
Section: Total Polyphenol and Flavonoid Contentsmentioning
confidence: 94%
“…The antioxidant activity was calculated using the formula given below. [20] % Free radical scavenging activity = [(A 0 -A s )/A 0 ] × 100 Where, A 0 is the absorbance of blank (DPPH solution alone) A 0 is the absorbance of extracts (DPPH + sample)…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%
“…[1] Since, plants reserve immeasurable secondary metabolites with multifaceted biological targets, the researchers are fascinated to explore their biological profile towards drug discovery. [2,3] seeds and other parts of the plants for microbial infections, wound healing, pain, fevers, rheumatoid arthritis, muscular spasm, sores, boils, etc. Pharmacologically the plant is proved to have antibacterial, antifungal, analgesic, anti-arthritic, and antiulcer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, diante dos dados aqui apresentados, percebeu-se que os extratos da planta foram capazes de produzir efeitos antimicrobianos sobre os microrganismos associados a etiologia da cárie dentária, como S. epidermidis (Chabi et al, 2014;Dias-souza et al, 2014); S. pyogens (da Silva et al, 2016), , S. oralis (Chabi et al, 2014) , S. aureus (Aguilar et al, 2012;Ajileye et al, 2015;Akin-Osanaiye & Anoze, 2018;Chabi et al, 2014;da Silva et al, 2016;Dias-souza et al, 2014;Santos et al, 2018;Liangpanth & Tongdeesoontorn, 2018;Rajesh et al, 2015;Saidu et al, 2012;Shobha et al, 2018;Sija et al, 2019;Thomas et al, 2015), e de bactérias relacionadas a etiologia da doença periodontal como Porphyromona gingivalis e a Prevotella intermedia (Varghese et al, 2013), além do Enterococcus faecalis, associado a infecções periapicais persistentes e falhas do tratamento endodôntico (Chabi et al, 2014;da Silva et al, 2016;Shobha et al, 2018;Thomas et al, 2015;Vasudev Ballal et al, 2015). Development, v. 9, n. 8, e883986459, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.6459 Além disso, destacam-se ainda seus efeitos sobre alguns fungos associados a candidose oral, como C. albicans (Shobha et al, 2018), C. pseudotropicalis (Ajileye et al, 2015) e C. tropicalis (da Silva et al, 2016).…”
Section: Metodologiaunclassified